2012
DOI: 10.1152/ajpregu.00453.2011
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution analysis of metabolic cycles in the intertidal musselMytilus californianus

Abstract: Inhabitants of the marine rocky intertidal live in an environment that alternates between aquatic and terrestrial due to the rise and fall of the tide. The tide creates a cyclical availability of oxygen with animals having access to oxygenated water during episodes of submergence, while access to oxygen is restricted during aerial emergence. Here we performed liquid chromatography and gas chromatography-mass spectrometry enabled metabolomic profiling of gill samples isolated from the California ribbed mussel, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
3
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 41 publications
4
69
3
2
Order By: Relevance
“…In a companion study, changes in metabolism were investigated by measuring changes in heart rate and by analysis of metabolite levels in the gills of the same mussels using mass-spectrometryenabled metabolomics (Connor and Gracey, 2012). The analysis of heart rates showed that animals enter a period of dramatically reduced cardiac activity, or bradycardia, during bouts of emersion, with the drop in heart rate occurring within minutes of being exposed to air.…”
Section: Biological Rhythms In An Intertidal Habitatmentioning
confidence: 99%
See 1 more Smart Citation
“…In a companion study, changes in metabolism were investigated by measuring changes in heart rate and by analysis of metabolite levels in the gills of the same mussels using mass-spectrometryenabled metabolomics (Connor and Gracey, 2012). The analysis of heart rates showed that animals enter a period of dramatically reduced cardiac activity, or bradycardia, during bouts of emersion, with the drop in heart rate occurring within minutes of being exposed to air.…”
Section: Biological Rhythms In An Intertidal Habitatmentioning
confidence: 99%
“…Together, these 'omics' studies provide the most comprehensive overview to date into how transcript and metabolite levels are orchestrated in mussels under a tidal regime, and show that ∼40% of the transcriptome exhibits rhythmic changes in abundance, with 80-90% of the rhythmic transcripts exhibiting a circadian 24 h oscillation (Connor and Gracey, 2011), while rhythmic changes in metabolite abundance are associated solely with a tidal 12 h oscillation (Connor and Gracey, 2012). Given the preponderance of circadian transcriptional rhythms in the intertidal mussels, it is surprising that no metabolites were detected that oscillate with a circadian rhythm.…”
Section: Biological Rhythms In An Intertidal Habitatmentioning
confidence: 99%
“…For example, Mytilus californianus exhibits noticeable metabolic rhythms during simulated tidal cycles (Connor and Gracey, 2012). In other invertebrates, such as decapod crustaceans, several reports show the existence of biological rhythms in locomotory activity and oxygen consumption (Naylor, 2010;Palmer, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Succinate is a tricarboxylic acid cycle (TCA) intermediate and is capable of donating electrons to the electron transport chain via oxidation to fumarate by succinate dehydrogenase (SDH). Decreased expression of SDH and increased levels of succinate are indicative of oxidative stress in shellfish when oxygen availability is limited (Tuffnail et al 2009 ;Anestis et al 2010 ;Connor and Gracey 2012 ), and when organisms are exposed to toxins (Wu et al 2013a ;Hanana et al 2014 ) or pathogens (Ji et al 2013 ;Wu et al 2013b ). Elevated tissue concentrations of succinate are also indicative of poor larval quality due to lower capacity for energy production (Young et al 2015b ).…”
Section: Discussionmentioning
confidence: 99%